Desenvolvimento da criatividade da criança: um diálogo com docentes da Educação Infantil - Canto, Fernanda Soares Godoi Yano do (2015)
This research investigates the relevance to work with creativity and how this can improve child s development, we analysed how teachers understand this and how they deal with creativity as an instrument to help them with the development of creativity in children; verified the conception that teachers have about teaching, planning and pedagogical practices that can help the development of creativity in child. Was conducted according to qualitative approach and the intrinsec study case. The methodological proceedings involved: data collecting, documental analysis; semistructured data interview with eight teachers from kindergarten. Teachers work with children from four to five years old and teach during morning and afternoon in a public kindergarten school in Mato Grosso do Sul. The analysis and data discussion were interpreted according to the answers (writing or oral) were given by interviewee. Next, the answers were separated by their characteristics related to the aims proposed by the research. The results revealed that teachers, despite of facing the lack of resources and technical support, are insecure about the conception of the development of creativity in child, they showed the necessity of understanding different representations of creativity and the correct methodology to work with in the current scenario. Thus, we recommend the review of curriculum during teacher s formation and new investments in continuous training of teachers in service.